Regio- and stereoselective biomimetic synthesis of oligostilbenoid dimers from resveratrol analogues: Influence of the solvent, oxidant, and substitution - Ibrahim Ali , Noorbatcha (Wiley-VCH Verlag GmbH & Co. KGaA, 2008)
Oligostilbenoids are polyphenols that are widely distributed in nature with multifaceted biological activities. To achieve biomimetic synthesis of unnatural derivatives, we subjected three resveratrol analogues to oligomerization by means of one-electron oxidants. Upon varying the metal oxidant (AgOAc, CuBr(2), FeCl(3)6 H(2)O, FeCl(3)6 H(2)O/NaI, PbO(2), VOF(3)), the solvent (over the whole range of polarities), and the oxygenated substitution pattern of the starting material, stilbenoid oligomers with totally different carbon skeletons were obtained. Here we propose to explain the determinism of the type of skeleton produced with the aid of hard and soft acid/base concepts in conjunction with the solvating properties of the solvents and the preferred alignment by the effect of pi stacking.